The role of the aromatic hydrocarbon receptor in the pathogenesis of atopic dermatitis - Pavel V. Gorodnichev (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The aromatic hydrocarbon receptor (AhR) is a cytoplasmic receptor and transcription factor that regulates a wide range of biological and toxicological effects by binding to specific ligands. Among the effects there is detoxification of xenobiotics, maintenance of tissue homeostasis, regulation of the immune response. The structure and functions of AhR are described in the review. The mechanisms of skin homeostasis with the participation of the aromatic hydrocarbon receptor such as the effect on oxidative reactions and participation in maintaining the barrier function of the epidermis are demonstrated in details. The role of AhR in the pathogenesis of atopic dermatitis is discussed. The participation of AhR in the implementation of immune mechanisms of this disease as well as in the regulation of the production of key proteins of the skin barrier is shown. The data on the therapeutic value of its pharmacological modulation including the results of clinical studies of the topical ligand AhR Tapinarof are presented. The role of the aromatic hydrocarbon receptor in the realization of the effect of phototherapy of atopic dermatitis is demonstrated.